Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5539/ijb.v6n4p139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening for E255K and F359V Mutations in Non-Responders Iraqi Chronic Myeloid Leukemia Patients to Imatinib Mesylate Therapy

Abstract: Mutations in the kinase domain (KD) of BCR-ABL are the most prevalent mechanism of acquired resistance to first generation of tyrosine kinase inhibitor Imatinib Mesylate (IM) in chronic myeloid leukemia (CML) patients. Dasatinib and Nilotinib, the second generation of tyrosine kinase inhibitors (SGTKI), have been approved for second-line treatment of CML patients who demonstrate resistance to IM. The identification of E255K and F359Vmutations, which are considered highly resistant to SGTKI nilotinib, lead to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…This disease was slightly more common in males than in females [14]. In this crosssectional study, patients mean age was 40.24±13.01 (25-75) years old with male: female proportion 1.02:1, Dhahii etal(2011) showed that Iraqi CML studies concerning the age and gender proportion were34.71±1.02 (9-70) years and male: female ratio was 1:1.62 [15] , while Jamal et al(2014); recorded a mean age of 40.45 ± 2.56 ranging from (25-75) years with male: female proportion 1.12:1 [16] .…”
Section: Discussionmentioning
confidence: 99%
“…This disease was slightly more common in males than in females [14]. In this crosssectional study, patients mean age was 40.24±13.01 (25-75) years old with male: female proportion 1.02:1, Dhahii etal(2011) showed that Iraqi CML studies concerning the age and gender proportion were34.71±1.02 (9-70) years and male: female ratio was 1:1.62 [15] , while Jamal et al(2014); recorded a mean age of 40.45 ± 2.56 ranging from (25-75) years with male: female proportion 1.12:1 [16] .…”
Section: Discussionmentioning
confidence: 99%